2016
DOI: 10.1136/bmjdrc-2015-000191
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes case finding in the emergency department, using HbA1c: an opportunity to improve diabetes detection, prevention, and care

Abstract: ObjectiveWe assessed the efficacy of routine glycated hemoglobin (HbA1c) testing to detect undiagnosed diabetes and prediabetes in an urban Australian public hospital emergency department (ED) located in an area of high diabetes prevalence.MethodsOver 6 weeks, all patients undergoing blood sampling in the ED had their random blood glucose measured. If ≥5.5 mmol/L (99 mg/dL), HbA1c was measured on the same sample. HbA1c levels ≥6.5% (48 mmol/mol) and 5.7–6.4% (39–46 mmol/mol) were diagnostic of diabetes and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…Although categorical agreement (no diabetes, prediabetes, diabetes) between morning plasma glucose and HbA1c was low in our study, most patients (92%) with a morning glucose <125 mg/dl had an HbA1c value <6.5%. Other studies have also described the use of fasting or random plasma glucose as a first step for screening inpatients for diabetes mellitus [10,[27][28][29]. Although the requirement of fasting for several hours (typically 8 hours) may be impractical in acutely ill hospitalized patients, in our setting we found that morning blood sampling results in most samples being fasting.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Although categorical agreement (no diabetes, prediabetes, diabetes) between morning plasma glucose and HbA1c was low in our study, most patients (92%) with a morning glucose <125 mg/dl had an HbA1c value <6.5%. Other studies have also described the use of fasting or random plasma glucose as a first step for screening inpatients for diabetes mellitus [10,[27][28][29]. Although the requirement of fasting for several hours (typically 8 hours) may be impractical in acutely ill hospitalized patients, in our setting we found that morning blood sampling results in most samples being fasting.…”
Section: Discussionmentioning
confidence: 65%
“…An informed consent was not required as this was a non-interventional study (the criteria used for obtaining HbA1c are in agreement with the indications for screening for diabetes mellitus according to standard guidelines [3]). Furthermore, many prior studies have validated the use of HbA1c measurement among hospitalized patients [6,[10][11][12][13][14][15][16][17][18]. Patients were informed about the results and if diabetes was detected were referred to the diabetology unit.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Another Australian study, in which HbA 1c was also assessed in patients with at least 5.5 mmol/L blood glucose, found that 38% of ED patients either had known diabetes or met the HbA 1c criterion for diabetes; diabetes had not previously been recognised in one-third of these cases. 15 Neither study examined documentation of diabetes or initiation of treatment. In a third Australian study, HbA 1c screening indicated that 5% of hospital inpatients aged 55 years or more had unrecognised diabetes.…”
Section: Discussionmentioning
confidence: 99%